Investigating the Impact of Climate Change on the Effective Indicators in Desertification and Predicting its Spatial Changes - Azam Sadat Hosseini Khezr Abad; Abassali Vali; Amirhossein Halabian; Mohammad Hossein Mokhtari; Seyyed Ali Mousavi (Desert)
Excessive dryness of arid regions has increased the intensity and spread of desertification. Investigating spatial and temporal patterns of desertification caused by climate change in the northwest of Yazd province using the Iranian model of desertification potential assessment (IMDPA) is one of the main objectives of this research. In this study, a twenty-year statistical period (2001-2020) was also selected as the base period to reveal climate change. And the precipitation and average temperature data collected from selected stations were downscaled with the BCC-CSM1-1 model from the CMIP5 series, under three radiative forcing scenarios RCP2.6, RCP4.5, and RCP8.5 using the LARS-WG6 simulator for the near future (period 2026-2055) and the far future (2071-2100). And the results of predicting climatic elements on the increase in the area of ​​areas prone to desertification in the studied region were evaluated. The results showed that the rainfall in the final decades of this century is lower than in the period 2026-2055 and in some places is increasing or decreasing compared to the average of the base period. Temperatures will increase relative to baseline for both future periods. Also, based on the IMDPA model, 80.54 percent of the area of ​​the region is in the severe desertification class in the base period. The intensity of climate-driven desertification in the distant future is more severe than in the near future and the base period. The largest changes in desertification classes in the near future are related to RCP2.6 and RCP4.5, and in the distant future are related to all scenarios. So that during this period, we will witness the transition and change of moderate and severe risk classes to severe and very severe classes, especially in RCP4.5. Therefore, at the end of this century, the intensity of desertification in the region will be more severe than in the base period and the near future.